Penerapan Pembelajaran P5 Berbasis Ecoprint Untuk Meningkatkan Kreativitas Membatik Siswa Kelas IV MI - Intan Nur Aulia; Benny Angga Permadi (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study was motivated by the low level of student creativity in arts learning, particularly in batik-making, and the limited use of methods that integrate local culture and environmental sustainability. This research aims to describe the implementation of the Pancasila Student Profile Strengthening Project (P5) using the ecoprint technique and to determine its effectiveness in improving the creativity of fourth-grade students at MI Miftahul Huda Kutorejo. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model conducted in two cycles with 12 student participants. Data were collected through observation, creativity questionnaires, documentation, and assessment of ecoprint products using Torrance’s four creativity indicators: fluency, flexibility, originality, and elaboration. The results showed an improvement in student creativity across cycles. In Cycle I, the average creativity score was 2.65, categorized mostly as Developing as Expected (BSH). In Cycle II, the average increased to 3.70, with 10 students reaching the Very Well Developed (BSB) category. These findings indicate that the P5 learning model using the ecoprint technique is effective in enhancing student creativity in terms of idea development, color selection, use of natural materials, and artistic expression.